2013
DOI: 10.1002/jgrd.50362
|View full text |Cite
|
Sign up to set email alerts
|

An observed negative trend in West Antarctic accumulation rates from 1975 to 2010: Evidence from new observed and simulated records

Abstract: [1] Observations of snow accumulation rates from five new firn cores show a negative trend that is statistically significant over the past several decades across the central West Antarctic ice sheet (WAIS). A negative temporal trend in accumulation rates is unexpected in light of rising surface temperatures as well as model simulations predicting higher accumulation rates for the region. Both the magnitude of the mean accumulation rates and the range of interannual variability observed in the new records compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 70 publications
(100 reference statements)
6
31
0
Order By: Relevance
“…While the recent period is relatively high, radar-derived annual accumulation shows no significant trend over Thwaites Glacier between 1980. While recent work by Burgener et al (2013) found a negative trend in several shallow cores straddling the divide between the Ross Sea and Amundsen Sea drainages, the three cores presented in this work indicate that accumulation rates within the Pine Island-Thwaites drainage system do not exhibit a recent trend, consistent with the snow radar record from Medley et al (2013).…”
Section: Study Areasupporting
confidence: 75%
“…While the recent period is relatively high, radar-derived annual accumulation shows no significant trend over Thwaites Glacier between 1980. While recent work by Burgener et al (2013) found a negative trend in several shallow cores straddling the divide between the Ross Sea and Amundsen Sea drainages, the three cores presented in this work indicate that accumulation rates within the Pine Island-Thwaites drainage system do not exhibit a recent trend, consistent with the snow radar record from Medley et al (2013).…”
Section: Study Areasupporting
confidence: 75%
“…4b). There is, however, some agreement with new in situ data from ice cores (Medley et al, 2013;Burgener et al, 2013). It should be remarked that in the ASE, where we also observe an ice loss maximum, the statistical framework might have difficulty in partitioning SMB and ice dynamics.…”
Section: Discussionmentioning
confidence: 52%
“…While the WDC results support a coherent response of temperature and accumulation at multi-millennial timescales, the timescale of interest for future sea level is centennial. Modern observations have shown that despite rapid warming in central West Antarctica over the past~60 years [Steig et al, 2009;Bromwich et al, 2013], there has been no discernible increase in accumulation [Medley et al, 2013;Burgener et al, 2013]. In Dronning Maud Land in East Antarctica, a similar disconnect has been observed; large positive accumulation anomalies in 2009 and 2011 are associated with only muted temperature increases [Lenaerts et al, 2013].…”
Section: 1002/2016gl068356mentioning
confidence: 95%
“…Modern observations of accumulation and temperature in Antarctica have not shown a consistent relationship because of large interannual variability in both parameters [e.g., Monaghan et al, 2006;Lenaerts et al, 2013] and because of limitations in the available reanalysis data [Nicolas and Bromwich, 2011b;Bromwich et al, 2011]. In central West Antarctica, which has experienced pronounced recent warming [Steig et al, 2009;Orsi et al, 2012;Bromwich et al, 2013], there has been no discernible increase in accumulation [Medley et al, 2013;Burgener et al, 2013].…”
Section: Introductionmentioning
confidence: 99%